Toll‐like receptor 4 signaling in hematopoietic‐lineage cells contributes to the enhanced activity of the human vaccine adjuvant AS01. Issue 12 (26th September 2019) - Van Maele, Laurye; Fougeron, Delphine; Cayet, Delphine; Chalon, Aurélie; Piccioli, Diego; Collignon, Catherine; Sirard, Jean‐Claude; Didierlaurent, Arnaud M
Abstract: The 3‐ O ‐desacyl‐4'‐monophosphoryl lipid A (MPL) activates immunity through Toll‐like receptor 4 (TLR4) signaling. The Adjuvant System AS01 contains MPL and is used in the candidate malaria vaccine and the licensed zoster vaccine. Recent studies reported that AS01 adjuvant activity depends on a transient inflammation at the site of vaccination, but the role of stromal or structural cells in the adjuvant effect is unknown. We investigated this question in mouse models by assessing the role of TLR4 on hematopoietic versus resident structural cells during immunization with AS01‐adjuvanted vaccines. We first established that TLR4‐deficient animals had a reduced immune response to an AS01‐adjuvanted vaccine. Using bone marrow chimera, we consistently found that Tlr4 expression in radio‐sensitive cells, i.e., hematopoietic cells, was required for an optimal adjuvant effect on antibody and T‐cell responses. At day 1 after injection, the pro‐inflammatory reaction at the site of injection was strongly dependent on TLR4 signaling in hematopoietic cells. Similarly, activation of dendritic cells in muscle‐draining lymph nodes was strictly associated with the radio‐sensitive cells expressing Tlr4 . Altogether, these data suggest that MPL‐mediated TLR4‐signaling in hematopoietic cells is critical in the mode of action of AS01. Abstract : The Adjuvant System AS01 potentiates innate and adaptive immunity by stimulating both the hematopoietic and structural cells in muscles and lymph nodes. MPL in AS01 mediates adjuvant activity through TLR4 signaling. Using bone marrow chimeric mice, the contribution of TLR4 to the adjuvant activity was found to be mainly driven by the hematopoietic compartment, in particular DC activation and induction of antigen‐specific T cells.